2014
DOI: 10.1039/c4cp02633k
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic–hydroxyl interaction of an alpha-aryl ether lignin model-compound on SBA-15, present at pyrolysis temperatures

Abstract: An aromatic alpha-aryl ether compound (a benzyl phenyl ether analogue) was covalently grafted to mesoporous silica SBA-15, to create BPEa-SBA-15. The BPEa-SBA-15 was subjected to successive heating cycles up to 600 °C, with in situ monitoring by DRIFTS. It was found that the toluene moiety coordinates to SBA-15 surface silanol hydroxyl groups via an aromatic-hydroxyl interaction. This interaction is evidenced by a red-shift of the aromatic C-H stretches, as well as a red-shift and broadening of the surface hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Recently, BA oxidation was carried out at 110 • C with the same Pd loading (about 0.7 wt.%) to compare these supports and GC had the highest activity (30,137 mol/h mol Pd , 11,267 mol/h mol Pd and 6910 mol/h mol Pd for Pd/GC, Pd/AC and Pd/CNT, respectively) [72]. The authors interpreted these results as meaning that the π-electron interaction between the aromatic group and graphene resulted in a higher adsorption of reactant alcohol and oxygen promote undeniably the aerobic oxidation reaction, a concept that has also been reported for aromatics on hydroxyl groups [73]. Another study reported that Pd NPs supported on graphene nanocomposite achieved selective oxidation of BA with 100% conversion and over 99% selectivity to benzaldehyde [74].…”
Section: Carbonmentioning
confidence: 75%
“…Recently, BA oxidation was carried out at 110 • C with the same Pd loading (about 0.7 wt.%) to compare these supports and GC had the highest activity (30,137 mol/h mol Pd , 11,267 mol/h mol Pd and 6910 mol/h mol Pd for Pd/GC, Pd/AC and Pd/CNT, respectively) [72]. The authors interpreted these results as meaning that the π-electron interaction between the aromatic group and graphene resulted in a higher adsorption of reactant alcohol and oxygen promote undeniably the aerobic oxidation reaction, a concept that has also been reported for aromatics on hydroxyl groups [73]. Another study reported that Pd NPs supported on graphene nanocomposite achieved selective oxidation of BA with 100% conversion and over 99% selectivity to benzaldehyde [74].…”
Section: Carbonmentioning
confidence: 75%
“…This is supported by DFT calculations that show that SHA and BHA prefer to orient with the aromatic rings more parallel to the interface, where vSFG signals would vanish due to in-plane rotational isotropy. Bands near 2,850–2,950 cm −1 are associated with vibrations in the respective ligands and can be attributed to a redshifted O-H stretch of the carboxylic acid or phenolic groups or aromatic C-H stretches ( Doughty et al, 2017 ; Gotch et al., 1991 ; Kandziolka et al., 2014 ). DFT results presented above support the possibility that these peaks are O-H stretches, whereas Raman measurements ( vide infra ) suggest there might be some weakening of the aromatic ring that would lower the C-H stretching frequency.…”
Section: Resultsmentioning
confidence: 99%
“…As compared to cellulose, hemicellulose and lignin pyrolysis investigation started receiving attention much later (Bährle et al, 2014;Collard and Blin, 2014;Kandziolka et al, 2014). Huang et al (2012) used xylose as a model compound to investigate pyrolysis pathways of hemicellulose, implementing DFT methods.…”
Section: Hemi-cellulose and Lignin Pyrolysismentioning
confidence: 99%